Pemahaman Perkembangan Filsafat Ilmu dan Teologi dalam Sejarah Pemikiran Manusia - Adhis Mareta; Timotius Sukarna (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Human thought has always evolved over time, especially in two very fundamental areas: philosophy of science and theology. Philosophy of science explores the nature of the mind and the methodology behind human knowledge, while theology seeks meaning and a relationship with transcendent forces. This article will discuss the evolution of these two fields throughout the history of human thought.